PENGEMBANGAN VIDEO PEMBELAJARAN IPA UNTUK KELAS IV SDN - Ismailah Ismailah (Jurnal Ilmiah Mandala Education (JIME), 2020)
Learning must be carried out in an interactive, innovative and fun way so that students do not feel bored when following the subjects presented. This study aims to design a learning video for the fourth grade natural science subjects on the subject of the least common multiple and the greatest common factor. This research was conducted in Tanah Tinggi 06 Petang Elementary School, Central Jakarta.  The research methodology used research and development with the ADDIE model approach which contains five steps; a) Analysis, b) Design, c), Develop, d), Implement, e). Evaluate. Data collection using questionnaires and tests, the validator consists of two experts and one teacher. The results of the validation of learning videos are categorized as good and learning video products are suitable for use in larger groups.